MYX: Runtime correctness analysis for multi-level parallel programming paradigms - Protze, Joachim; Tsuji, Miwako; Terboven, Christian; Dufaud, Thomas; Murai, Hitoshi; Petiton, Serge; Emad, Nahid; Müller, Matthias; Boku, Taisuke (Software for Exascale Computing - SPPEXA 2016-2019, 2020)
In recent years the increasing compute power is mainly provided by rapidly increasing concurrency. Therefore, the HPC community is looking for new parallel programming paradigms to make the best use of current and upcoming machines. Under the Japanese CREST funding program, the post-petascale HPC project developed the XcalableMP programming paradigm, a pragma-based partitioned global address space (PGAS) approach. To better exploit the potential concurrency of large scale systems, the mSPMD model was proposed and implemented with the YvetteML workflow description language. When introducing a new parallel programming paradigm, good tool support for debugging and performance analysis is crucial for the productivity and therefore the acceptance in the HPC community. The subject of the MYX project is to investigate which properties of a parallel programming language specification may help tools to highlight correctness and performance issues or help to avoid common issues in parallel programming in the first place. In this paper, we exercise these investigations on the example of XcalableMP and YvetteML.